The diverse roles of vitamin E, its occurrence and regulation in different plant tissues - Georgiadou, Egli C.; Manganaris, George A.; Fotopoulos, Vasileios (My University, 2020)
Fruits and vegetables contain vitamins, dietary fibre and phytochemicals, which promote human health. Specifically vitamins are major bioactive compounds, divided in water-soluble (vitamins B and C) and fat-soluble (vitamins A, D, E and K) ones, having strong antioxidant potential and limiting several diseases, including cancer and cardio-vascular diseases. Furthermore, vitamins play a key role in plant protection against abiotic and biotic stress factors. Vitamin E is a group of eight fat-soluble compounds known as tocochromanols, which are synthesized exclusively by photosynthetic organisms. Tocochromanols are categorised into two groups – tocopherols and tocotrienols. Each group contains four forms identified by prefixes α-, β-, γ- and δ-, yielding a total of eight forms. Vitamin E is an essential, lipid-soluble antioxidant in the human diet, protecting from cancer, diabetes, cardiovascular and neurological diseases. This review summarizes the recent developments in understanding the variety of roles of vitamin E as well as its major genetic regulatory pathways in plants. In addition, a comprehensive mapping of vitamin E occurrence is presented in different plant tissues, organelles and horticultural crop species, as well as throughout different stages of fruit development and at postharvest.
Zróżnicowane znaczenie witaminy E, jej występowanie oraz funkcje regulacyjne w różnych tkankach roślinnych
Keywords: Tocochromanols; Tocopherols; Tocotrienols; Vitamin E